(untitled) (Journal of Economic Research & Business Administration, 2016)
The article analyzes the intellectual capital, which has a radical impact on the development of innovative economy. At the present stage the intellectual capital has particular importance, it determines the structure of the national economy, the quality of products and services, the efficiency of the economy. The ability of the economy to create and use intellectual capital increasingly influences the economic strength of the nation and its prosperity. Survey Methodology. The basis for the article served as theoretical and applied research of foreign and domestic scholars and experts in the field of social responsibility, as well as legislative and regulatory documents in the field. In preparing the article used the traditional methodological tools of social science: the method of system analysis, the method of expert estimations, the method of scientific abstraction, etc. Results: theoretical analysis of the publications of scientists and experts led to the conclusion that in the economic studies the concept of “intellectual capital” is closely related to such concepts as intellectual resources, intellectual potential, human capital and they often used as identical concepts. Intellectual capital inherents in your own content, determined by the specifics of its functions. They are existence and progressive development of intellectual property, creative mindset. Intellectual capital is increasingly seen as a source of sustainable competitive advantage in relation to innovation.